1976
DOI: 10.1007/bf02876940
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and biosynthesis of secondary metabolites

Abstract: The relationship was studied between the energy metabolism of the actinomycete Streptomyces aureofaciens and the biosynthesis of chlorotetracycline by this organism. The energy charge values in a culture of low-production strain were almost identical with those of a production variant but the total sum of adenylates was about 10 times higher. In the stationary growth phase both strains evinced a drop in energy charge values followed by a rise to the original level. An increase in the concentration of inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…5H20, 0.001 g; ZnSO47H20, 0.01 g-, ferric ammonium citrate, 3.0 g; Betaine hydrochloride, 5.0 g; L-sodium glutamate, 20.0 g; glucose, 35.0 g; CaCO3, 3.0 g; methyloleate, 3.0 g; and K2HPO4, 2.3 g. Growth conditions and assay procedures were as previously described (Gray and Bhuwapathanapun, in press).…”
Section: Methodsmentioning
confidence: 99%
“…5H20, 0.001 g; ZnSO47H20, 0.01 g-, ferric ammonium citrate, 3.0 g; Betaine hydrochloride, 5.0 g; L-sodium glutamate, 20.0 g; glucose, 35.0 g; CaCO3, 3.0 g; methyloleate, 3.0 g; and K2HPO4, 2.3 g. Growth conditions and assay procedures were as previously described (Gray and Bhuwapathanapun, in press).…”
Section: Methodsmentioning
confidence: 99%
“…The biosynthesis of natural products produced by most actinomycetes is affected by phosphate concentrations in the medium ( Romero-Rodríguez et al., 2018 ; Martín et al., 2012 ; Solans et al., 2019 ). Initially, the phosphate effect was attributed to a decrease or inhibition of natural product production as a result of a phosphate increase in the culture medium ( Curdová et al., 1976 ). Further studies on phosphate metabolism-related genes identified several of these genes, such as alkaline phosphatase, polyphosphatase, and low- and high-affinity transporter genes, and the pho regulon ( Moura et al., 2001 ; Vuppada et al., 2018 ; Santos-Beneit et al., 2008 ; Martínez-Castro et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%